STRATEGI PETANI KARET DALAM MEMENUHI KEBUTUHAN HIDUP DI NAGARI TARUANG-TARUANG KECAMATAN RAO KABUPATEN PASAMAN (JURNAL SPASIAL, 2014)
This study aims to gather information, analyze and discuss data on Strategies rubber farmers in meeting the needs of life in Kenagarian Taruang-Taruang districts Rao Pasaman district. This research is descriptive qualitative techniques. To answer this problem used secondary data and primary data. Primary data was collected through observation, interviews, discussions with rubber farmers. The study concluded that: 1) People Nagari Tarung-Tarung have rubber land on average 2-5 hectares, the number of plants owned rubber generally 300 stems / ha, the average distance between the rubber plantation is 2-5 km from the farmhouse. Tools commonly used knives, machetes and hoes, 2) If more rain than the summer, the harvest will be disturbed, to overcome this is usually done fertilization, while the average frequency of harvest by the farmers is 1 time in 2 days, 3) production of rubber farmers in Nagari Tarung-Tarung generally is pure rubber because the selling price was good, generally sold to toke / traders who have a subscription, 4) Income rubber farmers sourced from rubber plantations, the highest selling price obtained farmers from the sap of pure, without mixture. Rubber prices are normal can meet the needs of farmers, but the farmers are not trying to sell directly to the factory rubber. Stable prices because there is no middleman and 5) Alternative business other than farming communities rubber is mostly done in Nagari-Combat Combat is aquaculture, rice paddies and trade was done to reduce the risk in the event of prolonged rainy seasonKeywords: Farmers Strategy Rubber Meets Needs In Life